The importance of biochemical and ultrasound markers in prenatal diagnosis: current methods and development perspectives - Torbicki, Adam; Gaworek, Piotr; Korpalski, Michał; Pawlikowski, Krzysztof; Żygłowicz, Marek; Augustyn, Dominik; Pawluczyk, Maria; Marciniak, Mateusz; Trybuła, Alicja (Quality in Sport, 2025)
This paper explores the role of biochemical and ultrasound markers in prenatal diagnosis, emphasizing their importance in early detection of chromosomal and structural abnormalities in the fetus. It aims to characterize the most relevant diagnostic markers, evaluate the sensitivity and specificity of current methods, and discuss modern advancements such as non-invasive prenatal testing (NIPT). Biochemical and ultrasound markers remain fundamental tools in prenatal screening, providing crucial information for risk stratification and early intervention. The integration of traditional methods with advanced technologies such as NIPT offers a comprehensive approach to fetal health assessment. Continuous refinement of diagnostic algorithms and broader access to non-invasive testing are key directions for future development, aiming to improve both prenatal care quality and patient safety.